HUBUNGAN PELATIHAN DENGAN KINERJA KARYAWAN - Desy Setyorini; Achmad Syahlani (Universitas Muhammadiyah Bengkulu, 2023)
The purpose of this study was to examine the significance of the relationship and establish and test the linearity and significance of the simple linear regression equation between training and employee performance. The research was conducted at the Directorate of Transportation, National Development Planning Agency, Jakarta. The sample in this study were 42 employees. This study uses a causal survey method. The research data were then processed and analyzed using simple linear correlation and regression analysis techniques using the SPSS program. The results of this study indicate that: (1) There is a significant positive relationship between training and employee performance, with a correlation coefficient of 0.695; and (2) the simple linear regression equation Y = 14.552 + 0.412X is a significant linear regression equation to express a linear relationship between training (X) and employee performance (Y) at the Directorate of Transportation, National Development Planning Agency, Jakarta.